CD22 x Siglec-G Double-Deficient Mice Have Massively Increased B1 Cell Numbers and Develop Systemic Autoimmunity - Jellusova, Julia; Wellmann, Ute; Amann, Kerstin Ute; Winkler, Thomas; Nitschke, Lars (Journal of Immunology, 2010)
CD22 and Siglec-G are inhibitory coreceptors for BCR-mediated signaling. Although CD22-deficient mice show increased calcium signaling in their conventional B2 cells and a quite normal B cell maturation, Siglec-G-deficient mice have increased calcium mobilization just in B1 cells and show a large expansion of the 131 cell population. Neither CD22-deficient, nor Siglec-G-deficient mice on a pure C57BL/6 or BALB/c background, respectively, develop autoimmunity. Using Siglec-G X CD22 double-deficient mice, we addressed whether Siglec-G and CD22 have redundant functions. Siglec-G X CD22 double-deficient mice show elevated calcium responses in both B1 cells and B2 cells, increased serum IgM levels and an enlarged population of B1 cells. The enlargement of 131 cell numbers is even higher than in Siglecg(-/-) mice. This expansion seems to happen at the expense of B2 cells, which are reduced in absolute cell numbers, but show an activated phenotype. Furthermore, Siglec-G X CD22 double-deficient mice show a diminished immune response to both thymus-dependent and thymus-independent type 11 Ags. In contrast, B cells from Siglec-G X CD22 double-deficient mice exhibit a hyperproliferative response to stimulation with several TLR ligands. Aged Siglec-G X CD22 double-deficient mice spontaneously develop anti-DNA and antinuclear autoantibodies. These resulted in a moderate form of immune complex glomerulonephritis. These results show that Siglec-G and CD22 have partly compensatory functions and together are crucial in maintaining the B cell tolerance. The Journal of Immunology, 2010, 184: 3618-3627.